Comparison in Growth, Feeding, and Metabolism Between a Fast-Growing Selective Strain and a Cultured Population of Pearl Oyster (Pinctada fucata martensii) - Zhang, Xingzhi; Ye, Bingcong; Gu, Zhifeng; Li, Meng; Yang, Shouguo; Wang, Aimin; Liu, Chunsheng (Frontiers in Marine Science, 2021)
Pinctada fucata martensii is the main species cultured for marine pearls in the world. A breeding program for desirable production traits, including growth rate was carried out, and a fast-growing selective strain of pearl oyster was established. In the current research, we compared the growth characteristics between selective strain and the cultured population of P. f. martensii in Bei Hai, Guangxi Province, China. The selective strain was further divided into two specifications, large size (SL) and small size (SS), and several physiological and metabolic indexes, including feeding, respiration, excretion, and enzyme activities, were compared with cultured population (CL). The results showed that at the age of 6 months, pearl oysters in selective strain were 14.61% larger than the control group, and the proportion of large size (30-40 mm) was 59%, which was twice that of the cultured population (28%). SL with the rapid growth rate had a high clearance rate matching growth, and the value was about 1.8 times that of CL and 5 times that of SS. In addition, the activities of digestive enzymes (including amylase, pepsin and lipase) and growth related carbonic anhydrase enzymes in SL were higher than those in the other two groups (p < 0.05). SS with slow growth rate had the fastest oxygen consumption rate and ammonia excretion rate, which were significantly higher than SL and CL (p < 0.05). These results suggested that rapid growth of selective strain P. f. martensii was attributed to increasing energy intake and reducing energy consumption. This study provides a physiological and energetic explanation for the growth improvement of selective strain in pearl oyster.